(untitled) (The Conference Hub, 2025)
Metabolic syndrome (MS) in children and adolescents is a combination of risk factors predisposing to the development of cardiovascular diseases and type 2 diabetes mellitus. The main components of MS are abdominal obesity, insulin resistance, arterial hypertension and dyslipidemia. In recent decades, there has been an increase in the prevalence of MS among children, which is associated with an increase in obesity and a sedentary lifestyle [2].